The Influence of Teacher Competence and Students’ Learning Motivation on Islamic Education (PAI) Learning Outcomes at SMAN 1 Negeri Katon, Pesawaran Regency - Icha Mufassiroh Asy-Syauqi; Syaiful Anwar; Mujib Mujib (Perkumpulan Dosen Tarbiyah Islam Indonesia, 2026)
This study aims to analyze the influence of teacher competence and students’ learning motivation on the learning outcomes of Islamic Religious Education (PAI) at SMAN 1 Negeri Katon, Pesawaran Regency. This research employs a quantitative approach with a correlational design. The population of the study consists of all 11th-grade students, totaling 206 students, with a sample of 136 students selected through a specific sampling technique. Data were collected using questionnaires to measure the variables of teacher competence and learning motivation, as well as documentation to obtain data on PAI learning outcomes. Data analysis was conducted using simple and multiple regression tests, preceded by prerequisite tests, including validity, reliability, normality, and linearity tests. The results of the study indicate that teacher competence has a positive and significant effect on PAI learning outcomes. Students’ learning motivation is also proven to have a positive and significant effect on PAI learning outcomes. Simultaneously, teacher competence and students’ learning motivation make a significant contribution to the improvement of PAI learning outcomes. These findings suggest that enhancing the quality of teacher competence, accompanied by strengthening students’ learning motivation, can optimally improve learning achievement. Based on these findings, it is recommended that future researchers examine other variables that may influence learning outcomes, such as the learning environment, instructional strategies, and family support. Furthermore, future studies are encouraged to expand the research subjects across different educational levels and contexts to enhance the generalizability of the findings.